2019
DOI: 10.1590/1809-4422asoc0328vu19l4ao
|View full text |Cite
|
Sign up to set email alerts
|

Health Risks Perception in the Context of the Construction of a Petrochemical Complex in Brazil

Abstract: This paper discusses the health risks perception in the surrounding from the construction areas of a Petrochemical Complex. The study aimed to determine the factors that lead to the health risks perception of the process of construction of the Petrochemical Complex of Rio de Janeiro. Cross-sectional study conducted with 240 individuals in Brazil’s southeast region. It was found that female adult individuals with a high level of schooling and residing in the surrounding of the Complex are capable of perceiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…These results are consistant with previous literature stating that those living close to the oil refinery continue to report negative health impacts and viewed odor perception and annoyance as vital elements in ill health reporting. 10 Furthermore, the perceived risk associated with chemicals and their industrial emissions usually turns into a generalized stress 33 or into emotional responses such as fear of cancer. 34 We asked a question regarding enjoying the place where they live and found that Bal'ma residents reported a substantially higher rate of enjoyment feeling compared to Al-Hashimeya residents (OR = 14.47; 95%CI: 8.07-25.93).…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistant with previous literature stating that those living close to the oil refinery continue to report negative health impacts and viewed odor perception and annoyance as vital elements in ill health reporting. 10 Furthermore, the perceived risk associated with chemicals and their industrial emissions usually turns into a generalized stress 33 or into emotional responses such as fear of cancer. 34 We asked a question regarding enjoying the place where they live and found that Bal'ma residents reported a substantially higher rate of enjoyment feeling compared to Al-Hashimeya residents (OR = 14.47; 95%CI: 8.07-25.93).…”
Section: Discussionmentioning
confidence: 99%